THE ECONOMIC AND SOCIOCULTURAL ROLE OF LIVESTOCK IN THE WELLBEING OF RURAL COMMUNITIES OF TIMOR-LESTE - Bettencourt, Elisa Maria Varela (2014)
The livestock species play very important economic and socio-cultural roles for the wellbeing of rural households, such as food supply, source of income, asset saving, source of employment, soil fertility, livelihoods, transport, agricultural traction, agricultural diversification and sustainable agricultural production. The aim of this work was to identify and characterize the different roles that livestock and livestock species play in rural communities of Timor-Leste, highlighting the importance of animal production for the wellbeing and rural development, and relate the functions performed by livestock production with economic, social and cultural attributes of the communities. The data used in this study were collected in 2011 through a questionnaire survey in three rural communities in the district of Bobonaro -mountain area, irrigation plain and coastal zone, and were complemented with secondary data. Livestock production in Timor-Leste is predominantly familiar being chickens, pigs, goats, cattle, horses, buffaloes and sheep the main species. Beyond the economic function, each livestock species also performs social and cultural functions.